State Policy on Islamic Education During the New Order Era and Its Implications for SDGs - Mohamad Muhsan; Faridi; Tobroni; Abdulhafiz Hile; Usamarn Madami; Mahmudulhassan (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to understand the Islamic education policy implemented during the New Order period, the challenges faced in its implementation, and its long-term impact on the development of Islamic education in Indonesia to date. By evaluating these policies within the broader context of national development, the study also examines their relevance to Sustainable Development Goals (SDGs), particularly SDG 4: Quality Education. Theoretical framework: This research is grounded in the theoretical framework of education policy and state–education relations, focusing on how political regimes exert control over religious education and integrate it into the national education system. The study also draws on theories related to educational equity and sustainable development to bridge the historical analysis with contemporary global goals. Literature review: The literature review includes a wide range of sources focusing on the New Order regime's political control, state-Islamic education relations, and the evolution of madrassas and pesantren. It also considers studies on the global movement towards inclusive and equitable education as framed in the SDGs. Methods: This study uses a qualitative descriptive approach. Data were collected through literature review and analysis of government policy documents, academic journals, and historical records. The data were analyzed descriptively to understand the policy shifts, ideological motivations, and socio-political dynamics surrounding Islamic education during the New Order era. Results: The findings reveal that the New Order's Islamic education policy marked a shift toward formal recognition of madrassas and religious education. Nevertheless, this came with centralized political control, suppression of academic freedom, and the influence of developmentalist and capitalistic ideologies. Over time, Islamic education has shown resilience and adaptability, increasingly aligning with the general education system and the inclusive goals set forth in the SDGs. Implications: The study underscores the importance of designing inclusive education policies that respect religious identity and academic autonomy in order to achieve SDG 4 and promote long-term educational equity. Novelty: This research provides a fresh perspective on the intersection between authoritarian politics and religious education and its implications for achieving sustainable educational development in Indonesia.